VARIABILITAS GENETIK DAN HERITABILITAS KARAKTER MORFOLOGIS BEBERAPA GENOTIPE KENTANG - Pangemanan, Ventje; Runtunuwu, D. S.; Pongoh, J. (Universitas Sam Ratulangi, 2013)
ABSTRACT This study aimed to determine the genetic variability and heritability of morphological characters of some genotypes of potato at the Seed Station in Linelean Village, Modoinding of South Minahasa Regency. The results showed that, the relatively narrow range of genotypes variance for all the characters observed. The coefficient of variance genotypes for plant height, at 14, 42 and 56 DAP (Days After Planting) was relatively narrow, whereas at 7, 21, 28, 35 and 42 DAP relatively wide. For the character of the number of leaves at 7 and 14 DAP are wide and at 21, 28, 35, 42 and 49 DAP relatively narrow. For the character of leaf area at 7 and 14 DAP were wide and at 21, 28, 35, 42 and 49 DAP relatively narrow. For the character of the number of harvest tubers per plant and weight per tuber harvest were wide. Wide sense heritability were high for all the characters observed, except for plant height at 7 and 56 DAP were classified as moderate. Keywords: genotype variance, coefficient variance of genotype and heritability ABSTRAK Penelitian ini bertujuan untuk mengetahui variabilitas genetik dan heritabilitas karakter morfologis beberapa genotipe kentang di Balai Benih Desa Linelean Modoinding Kabupaten Minahasa Selatan. Hasil penelitian menunjukkan bahwa ragam genotipe tergolong sempit untuk semua karakter yang diamati. Koefisien ragam genotipe untuk karakter tinggi tanaman, pada 14, 42 dan 56 HST (Hari Setelah Tanam) tergolong sempit, sedangkan pada 7, 21, 28, 35 dan 42 HST tergolong luas. Untuk karakter jumlah daun pada 7 dan 14 HST tergolong luas dan pada 21, 28, 35, 42 dan 49 HST tergolong sempit. Untuk karakter luas daun pada 7 dan 14 HST tergolong luas dan pada 21, 28, 35, 42 dan 49 HST tergolong sempit. Untuk karakter jumlah umbi panen per tanaman dan berat per umbi panen tergolong luas. Heritabilitas arti luas semua karakter tergolong tinggi, kecuali untuk karakter tinggi tanaman pada 7 dan 56 HST yang tergolong sedang. Eugenia Volume 19 No. 2 Agustus 2013 Kata kunci: ragam genotipe, koefisien ragam genotipe dan heritabilitas